Consumers’ Determination of Red Meat and Meat Products Purchase Behaviour – City of Ankara Sample - Hasan Arısoy; Zeki Bayramoğlu (Turkish Journal of Agriculture: Food Science and Technology)
Nowadays, meat consuming level is an indicator of development of countries. The reason for this is the importance of animal proteins such as meat, milk and egg in human nutrition. People in Turkey do not get enough animal protein. Increase of meat and meat related product prices is effective on this. The purpose of this study is to bring up the purchase and consume behavior of consumers. Surveys completed in urban areas around city of Ankara are used primarily. Using Main Mass Ratio Based Simple Occurrence Probability Sampling method 338 families were interviewed. Completed surveys were separated into 3 groups; high, middle, low. As a result of the research, expense for food in total income is around %34. This ratio for families with low income is %53, for families with middle income is %35 and for families with high income is %33. It is found that as income levels of consumers raised, food expenses raise as well. But it shows that as income level increases, expense ratio for food decreases. Food reliability is the most effective factor on consumers’ decision of purchase. Studies show doubts of consumers about food reliability. It is understood that legal adjustments are not applied enough. Especially tight food inspections would be positive on consumer behavior.